Study of Sigma 3 BaZrO3 (210)[001] tilt grain boundaries using density functional theory and a space charge layer model - Kim, Ji-Su; Yang, Jin-Hoon; Kim, Byung-Kook; Kim, Yeong-Cheol (CERAMIC SOC JAPAN-NIPPON SERAMIKKUSU KYOKAI, 2015)
We studied Sigma 3 BaZrO3 (210)[001] tilt grain boundaries using density functional theory and a space charge layer model. Formation enthalpies of BaZrO3 and competing oxides were calculated using fitted elemental-phase reference energy (FERE) correction, and a stable region of BaZrO3, as functions of Ba and O chemical potentials, was determined. Grain boundary energies were evaluated as functions of Ba and O chemical potentials within the determined stable region of BaZrO3 from the FERE correction. Among the six tested grain boundaries, an energetically favorable nonstoichiometric grain boundary was determined. Based on the nonstoichiometric grain boundary, we calculated the electrostatic potential and concentrations of proton and oxygen vacancy using a space charge layer model. (C) 2015 The Ceramic Society of Japan. All rights reserved.
Keywords: TOTAL-ENERGY CALCULATIONS; DOPED BARIUM ZIRCONATE; CATION NONSTOICHIOMETRY; PROTON; CONDUCTIVITY